Integrating Mathematical Patterns in Muslim Fashion Design: a 4D-Based Edupreneurship Innovation - Arghob Khofya Haqiqi; Naili Luma’ati Noor; Wakhid Fitri Albar; Hidayah Mohd Fadzil (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2025)
The purpose of this study is to develop an innovation